Strengthening Pandemic Preparedness in Undergraduate Education through Curricular Reform: Post-COVID-19 Insights - Goderdzishvili, Dea; Nikoleishvili, Elza (European Scientific Journal, ESJ, 2025)
Aims and Scope: The COVID-19 pandemic exposed widespread educational gaps in preparing future healthcare professionals for public health emergencies. This study aimed to identify key curricular indicators for strengthening pandemic preparedness in undergraduate biomedical and health sciences education, with Georgia as a representative case study of a resource-constrained setting. Methods: A qualitative study was conducted using semi-structured virtual interviews with 33 educators from the programs of medicine, public health, nursing, dentistry, and pharmacy - 30 based in Georgian institutions and three international experts contributing to triangulation. Data collected between May and August 2024 were analysed using inductive thematic analysis with MAXQDA. Findings: Thematic analysis revealed three core areas for reform: (1) strengthening institutional readiness by embedding pandemic-focused content and simulation-based learning; (2) enhancing public health communication, including vaccine advocacy and crisis response messaging; and (3) expanding research and collaborative capacity through interdisciplinary and international engagement. Conclusion: This study offers practical, curriculum-level strategies to close educational gaps and strengthen pandemic preparedness in undergraduate biomedical and health sciences education. Using Georgia as a case example, the findings present a scalable reform framework that can strengthen system resilience and better prepare future professionals for public health emergencies.